FREQUENCY OF BLOOD TYPES FROM SYSTEMS АВ0 AND RHESUS FACTOR IN PATIENTS WITH CARCINOMA OF THE VAGINAE: FREQUENCY OF BLOOD TYPES FROM SYSTEMS АВ0 AND RHESUS FACTOR IN PATIENTS WITH CARCINOMA OF THE VAGINAE - Boichev, Milen; Todorov, Velislav; Boycheva, Maria; Georgiev, Volodia; Minkov, Cvetan; Georgieva , Rada (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The research included 115 female patients with carcinoma of the vagina (Ca vaginae). Their blood types belonging to the systems AB0 and Rhesus factor were studied. Comparing the control group of Bulgarian population statistically significant differences in the distribution of all types of AB0 system were detected. The increase in blood type A (with 23, 26% - to 66, 96%) and the decrease in blood type 0 (with 18, 54% - to 19, 13%) are especially obvious. There is no difference in Rh system. It can be assumed that having blood type A appears to be one of the risk factors for the emergence and development of the disease in the female patients.